COVID-19 Vaccination in those with mental health difficulties: A guide to assist decision-making in England, Scotland, and Wales. (October 2022) - Ross, Callum; Brown, Penelope; Brown, Christian; Chopra, Arun; Adshead, Gwen; Tracy, Derek; Towers, Kevin; McKay, Colin; Black, Isra; Forsberg, Lisa
There is currently no specific guidance addressing vaccine hesitancy in those with mental health difficulties in the United Kingdom. This is particularly problematic when one considers that individuals with serious mental illnesses are at greater risk of infection and have poorer health outcomes for a range of reasons. There are also many individual and system level barriers to vaccination in this group. When an affected adult lacks the capacity to make a decision for themselves, it often falls to healthcare professionals to make a decision on that person's behalf and in their best interests. This article explores this matter with regard to the law in practice in the English and Welsh, and Scottish, jurisdictions and consider this with relevance to the safest approach that doctors and other healthcare professionals should take in working with patients for whom mental disorder may impact on decision-making capacity. The article focuses on psychiatric inpatients, including those who are detained involuntarily, to consider whether, and in what circumstances, COVID-19 vaccination should be given to individuals who cannot or do not consent.